Development of an Optronic Aiming System for Target Tracking on the S60 57mm Cannon Weapon Control System Using a Camera - Andriyan, Nelif; Kusuma, Cahya (International Journal of Marine Engineering Innovation and Research, 2025)
The development of technological science towards the defense of a country is growing rapidly. The country needs increasingly advanced defense technology but is constrained by an increasingly large budget due to dependence on producing countries. The state provides opportunities for technocrats to carry out research that can later create a defense technology that is inexpensive and does not burden the state budget. The artificial S60 57mm cannon is one of the cannons that functions as an air attack deterrent. The operating system of this weapon is still manual. This research will design and prototype an automatic Weapon Control System on the S60 57mm gun. In this development using the Atmega 8 microcontroller is the controller and interface for transferring data from the camera (Optronic) to the servo motor. The result of the camera position (optronics) will be followed in real-time by the gun barrel. In designing a target tracking control system automatically using the proportional control method. The results of testing the ability of the servo motor as a camera driver to follow targets or moving objects with a maximum angular speed of 15.5 degrees/second at a speed of 0.3 seconds, the average frame rate of the camera are 60 fps. c. Based on testing the servo motor using the Atmega8 microcontroller support, the reading of the angle direction of the servo motor is displayed in the Delphi software. Based on the test results, there is a difference between mathematical calculations and measurements using an arc ruler. With mathematical calculations, there is a difference with a value of 1.06 degrees per 1 degree.